Lifetime histories of PTSD, suicidal ideation, and suicide attempts in a nationally representative sample of adolescents: Examining indirect effects via the roles of family and peer social support. (June 2017) - Rojas, Sasha M.; Bilsky, Sarah A.; Dutton, Courtney; Badour, Christal L.; Feldner, Matthew T.; Leen-Feldner, Ellen W.
Highlights: Examined the relation between PTSD and youth suicidal behavior via social support. PTSD was associated to suicidal ideation and suicide attempts. PTSD was indirectly associated to suicidal ideation via familial support. PTSD was not indirectly associated to suicidal ideation via peer support. PTSD was indirectly associated to suicide attempts via father support.